PERANAN DOSEN TANPA JABATAN FUNGSIONAL TERHADAP PENGEMBANGAN KREATIFITAS MAHASISWA DI UNIVERSITAS MUHADI SETABUDI - Muhammad Syaifulloh (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Lecturer Functional Position is a system of Academic Position obtained through a series of filings which includes Tri Dharma activities of universities. This study aims to determine the role of lecturers without functional position to the Student Creativity Development, if the lecturer without functional positions whose category does not have the authority to teach according to DIKTI regulations on Student Creativity Development, Dependent Variable (Y) in this research is Student Creativity Development, while Independent variable (Variable X) is a lecturer without a Functional Position. the method used is quantitative descriptive method. Affordable population in this research is the students of the Faculty of Economics and Business atMuhadi Setiabudi University, amounting to 69. Because the population number is less than 100. Then the total population taken all the samples, then this study using the total sample (census method) Instrument used to know the variable independent (X) lecturer without functional position and variable Dependen (Y) Student Creativity Development is using Questionnaire. Data analysis technique is done by using descriptive statistical method that is to present data of each variable singly, and inferential ststistik that is to test the research hypothesis. With One-Way ANOVA method, the hypothesis of the study was conducted at the level of significance α = 0.05 Keyword: Lecturer, Functional Position, Student Creativity Development